Religious mission and migration: “new communities” and Brazilian pentecostal churches abroad - L. Mariz, Cecília (2009)
From the time of its colonization Brazil was known only as a target for catholic missionaries, mainly of European origin, and later of protestant missionaries, mainly from the United States. But this picture has been changing: in recent times, Brazilian missionaries have gone abroad to spread their gospel in other countries. This article examines this new missionary flow and its relationship to the paths of Brazilian emigrants looking for jobs abroad. Based on data collected in Brazil, particularly among catholic groups in the so-called “new communities”, and pentecostal documents, the article puts forward a number of hypotheses on the meaning of the religious motivations for geographical displacement in the modern global context.